Introduction to the special issue: 20 years of the Institute of Popular Music - Laing, Dave (Popular Music History, 2008)
In 1988, the Institute of Popular Music (IPM) at the University of Liverpool was opened. It was the first specialist centre for popular music studies in Britain and one of the first in the world. This issue of Popular Music History is both a celebration of the twentieth anniversary of the IPM’s foundation and an exploration of its own history and research achievements.